COMPARATIVE CHARACTERISTICS OF FUNCTIONAL CORONARY RESERVE AND MYOCARDIAL INFARCTION RISK IN PATIENTS WITH THE CARDIAC X SYNDROME AND STENOTIC CORONARY ATHEROSCLEROSIS - V. I. Kostin; A. L. Murashkovsky; S. D. Efremov; O. Y. Bogdanov; Y. V. Krotikov; A. V. Klimenkova; M. V. Stihurova; I. A. Shibanova; R. S. Karpov (Российский кардиологический журнал)
The aim of this research was to study the functional coronary reserve and frequency of miocardium infarction in patients with cardiologic syndrome X (CX) in comparison with patients with stenosing atherosclerosis of coronary artery (ACA). 54 patients with CX and 83 patients with ACA were examined. Coronaroventriculography,veloergometry, echo, daily ECG monitoring were conducted. It was proved that functional coronary reserve in CX patients is lower than in ACA patients. However risk of miocardial infarction development is higher in ACA patients. In the first place, functional coronary reserve depends on state of terminal sectors of coronary arterial channel both in CX and ACA patients. At the same time risk of miocardial infarction development is above all conditioned by damage of subepicardial arteries, i.e. presence of atheromas in them and relatively little depends on volume of coronary channel’s damage.